Myths and Facts Concerning Labour Costs in Poland - Krajewska, Anna; Krajewski, Stefan (Olsztyn Economic Journal, 2015)
Many opinions have been expressed for years concerning labour costs in Poland. Unsurprisingly, those opinions have been far from consensus. Basically, low wages are treated as a factor increasing the competitiveness of our economy and it is argued that they constitute major proof that Poland is attractive for foreign investors. On the other hand, however, entrepreneurs and various organisations representing them have repeatedly pointed out that high labour costs in Poland are the principal cause of unemployment, growth of grey economy, and low competitiveness of the country's economy. The above problems assumed particular significance after Poland's accession to the European Union. Basing on statistical data and empirical research we try to verify some myths concerning the labour costs in Poland.